A financial valuation study of BMW AG - Heyerman, Bjoern (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Barriers to financial inclusion: a study of the economic Community of west African states - Té, Adjombi (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Melco Crown Entertainment Limited - Cheong, Man (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Comcast Corp - Vasu, Kadali (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The evaluation of Microsoft Corporation - Mendonça, César (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The valuation of Costco Wholesale Corporation (COSTCO) - Enomoto, Hiromi (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of unilever n.v - Bembom, Willem (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Las Vegas Sands Corp - Gomes, Sérgio (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Sands China Limited - Ieong, Sio Ian (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Las Vegas Sands - Ho, Chi Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business valuation of Ford company - Zhang, An Qi (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Hyatt Hotels Corporation - Lam, I. Leng (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of melco crown entertainment - Lam, O. Fu (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Caluation of Microsoft Coproration - Lee, Ka Lou (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Campbell Soup Company - Wong, Chong Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Study of the Valuation of ManpowerGroup Inc - Lei, Choi Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Yahoo! Inc - Hong, Nga Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Starbucks corporation - Ho, Chon In (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Las Vegas Sands Corp - Wu, Chi Leng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Coca Cola Company - Chan, Weng Chun (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Wal-Mart Stores, Inc - Ng, Mei Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Under Armour - Leong, Ka Wa (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Pepsico Incorporated - Cenon, Susan Gasque (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Marriott International, Inc - Ian, Kin Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Waste Management, Inc: Daniela Wai Ka, Leong - Leong, Wai Ka (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Ralph Lauren Corporation - Tse, Yin Man (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Tencent Holdings Limited - Leong, Weng Hong (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of McDonald's Corporation - Iao, Sok Mei (University of Saint Joseph, 2007)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of caterpillar incorporated - Chu, Un I. (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the adobe systems incorporated - Law, Kwun Kau (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Evaluation of Bally Technology Limited - Lao, Sio Mei (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The financial feasibility study of redevelopment project at Rua da Caldeira Number 22 - Cheong, Tat Hong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation: study of ecolab,inc - Io, Hei Lam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Wal-Mart Stores, Inc - Hun, Weng U. (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Alibaba Group Holding Limited - Chan, Man Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the news corporation - Kwan, Wai Sam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of GAP Inc - Cheong, Im Seong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Expedia, Inc - Lei, Lou Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Lenovo group limited - Sin, Si Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Coca Cola company - Kuan, U. Ian (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Tencent Holdings Limited - Tam, Wai Hou (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the xerox corporation - Lam, Kam Long (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Foot Locker, INC - Lam, Weng Ip (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation Study of AT&T, Inc - U, Weng Kei (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Trend and Characteristics of Deviant Behavior of Young People in Macao Between 2001 and 2019 - Sam, Lek I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Valuation of International Game Technology - Ho, Sao Kun (University of Saint Joseph, 2007)
Keywords: International Game Technology; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

Valuation of Wynn resorts, limited - Leong, Teng Hon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The study of financial valuation of Marriott International, Inc - Ao, Ka Ian (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of McDonald's Corporation - Wong, Wai I. (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Netflix, Inc - Tong, Si Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of 3M Company - Gilbert, Maria Cristina (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Tiffany & Co - Chu, Choi Peng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Seagate technology plc - Kam, Tao Choy (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Johnson & Johnson - Kuan, Hei Man (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of Yum! Brands, Inc - Chan, Hou Kit (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The financial valuation study of McDonald's, Inc - Ng, Wai Lon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Yum! Brands, Inc - Hun, Weng San (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Hewlett-Packard company - Lei, Weng Lon (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Shun Tak Holdings - Cheang, Wai Kei (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Novartis International AG - Pires, Dora Marques (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Ebay INC - Pong, Pou I. (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Wynn Resorts Limited - Li, Iok I. (University of Saint Joseph, 2016)
Keywords: Financial institutions Valuation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Wynn Resorts Limited

A financial evaluation of MGM Resort International - Lei, Pou I. (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of the Hershery Company - Ho, Weng Kam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of MGM Resorts International - Lei, Cheng I. (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of SJM Holdings Limited - Ng, Lin Kei (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of discovery communications - Wong, Mei Wan (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial Valuation of Nike - Cheong, Hio Fong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuing Walt Disney Co - Neves, Júlio Alexandre Dias (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Shun Tak Holdings - Magalhães, João Pinto de (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Wabtec Corporation - Pereira, Marcos da Silva (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Pfizer Inc - Pires, Rui Carlos Moreno (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of GOOGLE INC - Faria, João David Benazra (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of the Costco Wholesale corporation - Rato, Ricardo Jorge Parreira (University of Saint Joseph, 2006)
Keywords: Corporations; Costco Wholesale Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

The Walt Disney Company valuation "If you can dream it, you can do it" - Walt Disney - Pereira, Filipe Manuel Peixoto (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Foreign Pharmaceutical Companies in China: IPR and Investment - Ribeiro, Paulo Miguel Mateus Simões (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial Valuation Study for Moody’s Corporation - Sio, Lai Teng (University of Saint Joseph, 2023)
This study presents the intrinsic value of Moody’s Corporation, a leading credit rating agency in the U.S. The results of the valuation were compared to the market value of Moody’s Corporation of the same date. The aim of the research is to provide a perspective to the investors on whether the actual value of the Company was overvalued or undervalued in the market, and how much the volatility of the stock price by the change of some factors. Both qualitative and quantitative analyses were applied in the research. The historical data, economic outlook, and the Company’s strategies were collected to be the metrics to determine the intrinsic value and provide an analysis of the prospects of Moody’s Corporation. Three valuation models were applied in the research to estimate the intrinsic value of the Company’s common stock. The cost of debt, cost of equity, the weighted average cost of capital, and the market risk premium were introduced and calculated in the research as they were the critical components in the valuation process. Since the valuation was based on assumptions and historical data to determine future growth, which indicates that the results could be changed due to uncertain factors. This study demonstrates that there was some discrepancy between the stock’s market price and the intrinsic value per share of Moody’s Corporation as of December 31, 2021
Keywords: Intrinsic Value; Moody's; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

Financial valuation of Oracle Corporation - Monteiro, Amilcar Samora Rodrigues Rendall (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The VALUATION OF TENCENT HOLDINGS LIMITED - Lo, Hao Weng (University of Saint Joseph, 2023)
This study analyzed Tencent Holdings Limited’s internal and external factors and future strategies, forecasted the financial statements of the Company for the next ten years, and measured the intrinsic value of the Company on December 31, 2021 and compared it with the stock market price on the same date. The share price’s sensitivity analysis was also conducted to understand the Company's capital structure and profitability, and the sensitivity analysis can be used to reflect the impact of these factors and strategies on the future share price, which can have a high impact on investors' future investment decisions. This study also used the SWOT Analysis and Michael Porter's Five Forces Analysis to analyze the Company's strengths, weaknesses, opportunities and threats and the Five Competitive Forces that shape the technology industry to evaluate the Company's external and internal environment and enrich the management with a more intuitive analysis leading to recommendations
Keywords: PEST Analysis; SWOT Analysis; Technology Industry; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Realty Income Corporation - Rodrigues, Ricardo David Almeida Fernandes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Evaluation of Fluor Corporation - Cabaça, Anacleto de Jesus da Silva (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A FINANCIAL VALUATION OF ORACLE CORPORATION - Maung, Ye Thu Anug (University of Saint Joseph, 2023)
Oracle Corporation (hereinafter referred to as Oracle, ORCL, or ‘the Company’) is an American multinational company that provides solutions of products and services that serve the enterprises’ information technology (IT) environment. This thesis is to conduct a business analysis of the Company from a financial perspective, determining the Company’s intrinsic value as of May 31, 2021, and comparing it with the respective market value. Thus, this thesis will study, evaluate, and present an overview of the Company, an analysis of the Company’s market, industry, strategy, financial performance, including external and internal factors, a ten-year pro forma financial statement forecast, and the techniques of using the three discounted cash flow models to estimate the intrinsic value of Oracle. The obtained results from the three valuation models, including the Enterprise Discounted Cash Flow (EDCF) model, the Adjusted Present Value (APV) model, and the Discounted Economic Profit (DEP) model, show that the Company’s intrinsic values were estimated at $74.57, $75.21, and $74.82, respectively. When the results were used to compare with the market price of Oracle’s shares as of May 31, 2021, at $78.74, it reflects that the Company was overvalued
Keywords: Analysis; Financial Valuation; Oracle Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Starbucks Corporation - Kusnadi, Figo (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph